Home

Classrooms

Courses

About Us

Resources

Members

More

Simplify the following boolean algebra expression:

~~A+(~~B x ~~C)+~~A x ~~~B

=A+(B x C)A~B

=(A+BC)A~B

=AA~B+BCA~B

=A~B+~BBCA

=A~B+0

=A~B

~( ~ (A + BC) + ~ (A * ~ B)) = ~~(A + BC) * ~~ (A * ~ B) = (A + BC)(A * ~ B) = A + B*~BC = A

~( ~ (A + BC) + ~ (A * ~B)) = (~~(A + BC)(~~(A * ~ B)) = (A + BC)(A * ~B) = A(1 + BC)(~B) = A(~B)

~ ( ~(A + B*C) + ~(A * ~B))

= ~(~A * (~B + ~C) + ~A + B )

= ~( ~A * ~B + ~A * ~C + ~A + B)

= ~(~A*~B) * (A + C) * A * ~B

= (A + B) * (A +C) * A * ~B

=(A + A*C + B*A) * A * ~B

= (A + A*C + A* B) * ~B

=A*B~ + A*C*B

correction:

= ~ ~ (A + B*C) * ~ ~(A*~B)

= (A + B*C) * A * ~B

= (A + A * B * C) * ~B

= A * ~B

~~A+(~~B * ~~C) +~~A * ~~~B = A+(B*C)+A*~B

= A+B*C+A*~B

= A+B*C+0

= A+B*C

~~A+(~~B x ~~C) +~~A x ~~~B

=A+(B xC) + A x ~B

=A~b+0

=A~b

~(~(A + BC) + ~(A~B) )

= ~~(A + BC) ~~(A~B)

= (A + BC)A~B

= AA~B + BCA~B

= A~B + B~BCA

= A~B + 0

= A~B

~~A +(~~B x ~~C) + ~~A x ~~~B = A + (B x C) x A x ~b =(A x A + B x C x A) x ~B = (A + A x B x C) x ~B = A x ~B + A x C x B x ~B Answer = A x ~B

~~A +(~~B x ~~C) + ~~A x ~~~B

= A + (B x C) x A x ~b

=(A x A + B x C x A) x ~B

= (A + A x B x C) x ~B

= A x ~B + A x C x B x ~B

Answer = A x ~B

~~A+(~~B x ~~C)+~~A x ~~~B

=A+(B x C)A~B

=(A+BC)A~B

=AA~B+BCA~B

=A~B+~BBCA

=A~B+0

=A~B

~( ~ (A + BC) + ~ (A * ~ B)) = ~~(A + BC) * ~~ (A * ~ B) = (A + BC)(A * ~ B) = A + B*~BC = A

~ ( ~(A + B*C) + ~(A * ~B))

= ~(~A * (~B + ~C) + ~A + B )

= ~( ~A * ~B + ~A * ~C + ~A + B)

= ~(~A*~B) * (A + C) * A * ~B

= (A + B) * (A +C) * A * ~B

=(A + A*C + B*A) * A * ~B

= (A + A*C + A* B) * ~B

=A*B~ + A*C*B

~~A+(~~B * ~~C) +~~A * ~~~B = A+(B*C)+A*~B

= A+B*C+A*~B

= A+B*C+0

= A+B*C

~~A+(~~B x ~~C) +~~A x ~~~B

=A+(B xC) + A x ~B

=(A+BC)A~B

=AA~B+BCA~B

=A~b+0

=A~b

~(~(A + BC) + ~(A~B) )

= ~~(A + BC) ~~(A~B)

= (A + BC)A~B

= AA~B + BCA~B

= A~B + B~BCA

= A~B + 0

= A~B

~~A +(~~B x ~~C) + ~~A x ~~~B = A + (B x C) x A x ~b =(A x A + B x C x A) x ~B = (A + A x B x C) x ~B = A x ~B + A x C x B x ~B Answer = A x ~B

~~A +(~~B x ~~C) + ~~A x ~~~B

= A + (B x C) x A x ~b

=(A x A + B x C x A) x ~B

= (A + A x B x C) x ~B

= A x ~B + A x C x B x ~B

Answer = A x ~B